Application of forecasting methods in harmonising strategic planning for sustainable development of the state - Lesia Korolchuk (Economic Forum, 2024)
Successful implementation of the global concept of sustainable development requires harmonising the strategic planning of sustainable development of the state to ensure effective monitoring of the progress of states in achieving the Sustainable Development Goals. The purpose of the research is to actualise the problem of applying forecasting methods in the process of harmonising the strategic planning of the sustainable development of the state and to develop methodological tools for its solution. In the course of the study, based on the application of such methods as: literature review, hypothetical-deductive method, comparison method, empirical method and logical analysis, the expediency is substantiated, methodological tools are developed and the method of triple exponential Holt-Winters smoothing based on a long time series is tested using the Forecast Sheet in Microsoft Excel 2016. Within the framework of a harmonised approach to strategic planning for sustainable development, to assess the country's progress in sustainable development, the indicators of decoupling of environmental pressure from economic growth are used, as they are simple, measurable and flexible. Based on the Tapio's methodology, a norm of non-renewable resource decoupling and environmental impact decoupling indicators is determined as a benchmark for the development and analysis of the effectiveness of the national sustainable development strategy, and a forecast of the dynamics of these indicators in the EU as a whole until 2026 is made, as a leader in the greening of the economy. The findings allowed us to identify the main trends in the EU's sustainable development, basing on the classification of the decoupling status. The results obtained contribute to the harmonisation of national strategies to ensure the successful implementation of the global concept of sustainable development, can be used at such a stage of strategic planning as the formation of a goal tree, which makes it possible to set both attainable and relevant goals, as well as in assessing the effectiveness of strategies in achieving the Sustainable Development Goals
Keywords: 330; Sustainable Development Goals; exponential smoothing; decoupling; harmonised approach; national strategy; unification